Biomechanical comparison of different internal fixation devices for transversely unstable Mason type II radial head fractures - Zhang, Xiang; Gong, Ling; Ma, Hong; Liu, Jinhui; Duan, Xin (Frontiers in Bioengineering and Biotechnology, 2023)
Background: The integrity of the radial head is critical to maintaining elbow joint stability. For radial head fractures requiring surgical treatment, headless compression cannulated screw fixation is a less invasive scheme that has fewer complications. The aim of this study was to compare the mechanical stability of different fixation devices, including headless compression cannulated screws and mini-T-plates, for the fixation of transversely unstable radial head fractures. Methods: Forty identical synthetic radius bones were used to construct transverse unstable radial head fracture models. Parallel, cross, and tripod headless compression cannulated screw fixation and mini-T plate fixation were applied. The structural stiffness of each group was compared by static shear loading. Afterward, cyclic loading was performed in each of the three directions of the radial head, and the shear stability of each group was compared by calculating the maximum radial head displacement at the end of the cycle. Findings: The mini-T plate group had the lowest structural stiffness (51.8±7.7 N/mm) and the highest relative displacement of the radial head after cyclic loading (p < 0.05). The tripod headless compression cannulated screw group had the highest structural stiffness among all screw groups (p<0.05). However, there was no significant difference in the relative displacement of the radial head between the screw groups after cyclic loading in different directions (p>0.05). Interpretation: In conclusion, the biomechanical stability of the mini-T plate for fixation of transverse unstable radial head fractures is lower than that of headless compression cannulated screws. Tripod fixation provides more stable fixation than parallel and cross fixation with headless compression cannulated screws for the treatment of transversely unstable radial head fractures.